Case report: Successful outcome of COVID-19 in the context of autologous hematopoietic stem cell transplantation: The impact of the anti-SARS-CoV-2 vaccine and early remdesivir - Lasagna, Angioletta; Piralla, Antonio; Secondino, Simona; Sacchi, Paolo; Baldanti, Fausto; Bruno, Raffaele; Pedrazzoli, Paolo (Frontiers in Medicine, 2022)
Coronavirus disease (COVID-19) in the patients undergoing hematopoietic stem cell transplantation (HSCT) is a major issue. None of the published papers has reported data on the outcome of the HSCT patients with COVID-19 disease according to the vaccination status and the short course of remdesivir (RDV). Therefore, we present the case of a 22-year-old man with relapsed testicular non-seminomatous germ-cell tumor and COVID-19 infection diagnosed during his first auto-HSCT. Our case report is the first one describing the efficacy of early RDV (and its anti-inflammatory effects that might counterbalance the negative effect of the recombinant human granulocyte-colony stimulating factors -rhG-CSF-) in the context of a severe neutropenia following HSCT with the concomitant onset of COVID-19 disease.